Resveratrol prevented spatial deficits and rescued disarrayed hippocampus asymmetric dimethylarginine and brain-derived neurotrophic factor levels in young rats with increased circulating asymmetric dimethylarginine. Issue 13 (19th July 2021) - Hsu, Mei-Hsin; Chang, Kow-Aung; Chen, Yu-Chieh; Lin, I-Chun; Sheen, Jiunn-Ming; Huang, Li-Tung
Abstract : Increased plasma levels of asymmetric dimethylarginine can be encountered in chronic inflammatory disease, liver damage, renal failure, and multiple organ failure. In addition, an association between circulating asymmetric dimethylarginine levels and all-cause mortality has been reported. Male Sprague–Dawley rats, postnatal day 17 ± 1, received continuous asymmetric dimethylarginine infusion via an intraperitoneal pump. Spatial performance and dorsal hippocampal asymmetric dimethylarginine and brain-derived neurotrophic factor (BDNF) levels were examined, and the effect of resveratrol was tested. A 4-week continuous asymmetric dimethylarginine infusion in young male rats caused spatial deficits, increased asymmetric dimethylarginine levels, and decreased BDNF expression in the dorsal hippocampus. Increased oxidative stress and altered molecules in the dorsal hippocampus linked to asymmetric dimethylarginine and BDNF functions were detected. Resveratrol protected against these effects, reversing spatial deficits, and reducing the changes in the dorsal hippocampal asymmetric dimethylarginine and BDNF levels.